Polyembryony increases embryo and seedling mortality but also enhances seed individual survival in Handroanthus species (Bignoniaceae) - Mendes-Rodrigues, Clesnan; Sampaio, Diana Salles; Costa, Maria Eugenia; de Souza Caetano, Ana Paula; Ranal, Marli Aparecida; Bittencourt Junior, Nelson Sabino [UNESP]; Oliveira, Paulo Eugenio (Elsevier Gmbh, Urban & Fischer Verlag, 2012)
Polyembryony seems to be advantageous to mother plants in detriment of their siblings which face competition since the beginning of seed development. This competition may limit the turnover of embryos into seedlings and their survival ability. We analysed polyembryony frequency and embryo to seedling turnover in three Handroanthus species with sporophytic apomixis. We tested if the embryo number per seed affected seed and embryo morphometry, seedling survival ability and seed individual survival (i.e. survival of at least one seedling per seed): The number of embryos per seed was compared with seedling number at different developmental stages. All 14 populations showed high frequencies of polyembryonic seeds (21-91%). As the number of embryos per seed increased (up to eight embryos/seed), there was a reduction of mean embryo mass, area, seedling length, individual seedling survival ability, and embryo to seedling turnover. There was also an increase in embryo morphological anomalies. However, enhanced seed individual survival was also observed. Thus, the high frequency of polyembryonic seeds and the increase in seed individual survival support the idea that polyembryony represents an alternative reproductive mechanism which can favours these species. (C) 2012 Elsevier GmbH. All rights reserved.
Keywords: Competition; Embryo to seedling turnover; Morphological anomalies; Seed germination; Sporophytic apomixis; Tabebuia